Presymptomatic diagnosis in Portuguese FAP families using intragenic RFLPs and (CA)n flanking markers by fluorescence based semiautomated DNA analysis. Issue 3 (March 1996) - Almeida, R; Fidalgo, P; Ramalho, E; Brás, A; Leitão, N; Mira, C; Rueff, J; Monteiro, C
Abstract : Owing to the large size of the APC gene, responsible for familial adenomatous polyposis, direct screening for individual mutations is not a practical approach. In the present study we establish the methodology of fluorescence based semi-automated DNA analysis to perform presymptomatic diagnosis of members at risk from 11 Portuguese FAP families with three (CA)n markers flanking the APC gene, MBC, CB26, and YN5.64, and four intragenic RFLPs. Haplotypes were constructed on the basis of individual genotypes and their segregation through generations were followed. The study was informative for 12% of subjects using only intragenic RFLPs and increased to 90% when we used the three (CA)n flanking markers. We report two of the 11 families under study in our laboratory and show recombinant events leading to a precise localisation of the CB26 marker between D5S82 and the APC gene. In one family there was a loss of (CA) units of one allele of the CB26 marker from an unaffected mother to her son.